Problematika Penerapan Asas-Asas Umum Pemerintahan yang Baik dalam Keputusan Administratif - Sarifurohman; Bobi Wartono H.S; Maman Sukarso (PT. Hasba Edukasi Mandiri, 2026)
The General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB) constitute fundamental principles in administrative law that serve as both guidelines and limitations for government officials in making administrative decisions. This study aims to analyze the problems in the application of AUPB in administrative decision-making practices and to examine their juridical implications for the protection of citizens’ rights. This research employs a normative juridical approach by examining statutory regulations, particularly Law Number 30 of 2014 on Government Administration, administrative law doctrines, and relevant administrative court decisions. Data were collected through library research and analyzed using a descriptive qualitative method. The findings reveal that although AUPB has been normatively recognized as a standard for assessing the legality of administrative decisions, its implementation in practice remains inconsistent. Administrative decisions tend to emphasize formal legality while neglecting principles such as prudence, proportionality, and transparency. This condition weakens the protection of citizens’ rights and contributes to the increasing number of administrative disputes. The study highlights the importance of internalizing AUPB as a substantive guideline to ensure that administrative decisions are not only legally valid but also reflect justice, legal certainty, and governmental accountability.